EXPLORING THE VALUE OF TEMPLE ACCOUNTABILITY AND TRANSPARENCY PRACTICES - Dewa Gede Yudha Dananjaya; Basuki Basuki (Universitas Airlangga, 2019)
Tanah Lot which is based on a precept of morality in it. This study uses a qualitative methodology, with an interpretive paradigm and by using a case study approach. The results of accountability carried out by managers have been documented, accountability refers to the practice of the teachings of tri hita karana and managers involve external parties in their management. Weaknesses are still visible where the manager is still using the manual ticket system. Then the transparency carried out by managers is still lacking, especially in terms of their finances which tend to seem closed.